Mitigasi Risiko Kasus Keracunan Program MBG di Kota Padang Panjang - Siti Nurul Salma; Sufia Shalehah; Azhara Fetri Stevana; Fadilah Fadilah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The Free Nutritious Meal Program (MBG) is a government policy aimed at improving health and fulfilling the nutritional needs of students at school. However, its implementation is not free from various food safety risks. The suspected poisoning cases that occurred among several elementary and middle school students in Padang Panjang City in October 2025 highlight the importance of comprehensive supervision during the food serving process. Laboratory test results found that MBG food was safe for consumption, but there was contamination of coliform bacteria in the refillable drinking water provided at the school. This indicates that sanitation factors and the cleanliness of the food serving environment also play a role in triggering health issues. This article discusses the potential risks in the MBG program, the causative factors in the Padang Panjang case, as well as relevant risk mitigation strategies, such as routine drinking water inspections, strengthening hygiene SOPs, hygiene education for students, and inter-agency coordination. Risk mitigation is an important step to ensure food safety, prevent similar incidents, and support the sustainability of the MBG program in the future.